Is comprehensive geriatric assessment hospital at home a cost-effective alternative to hospital admission for older people?. (31st December 2021) - Singh, Surya; Gray, Alastair; Shepperd, Sasha; Stott, David J; Ellis, Graham; Hemsley, Anthony; Khanna, Pradeep; Ramsay, Scott; Schiff, Rebekah; Tsiachristas, Apostolos; Wilkinson, Angela; Young, John
Abstract: Background: hospital level healthcare in the home guided by comprehensive geriatric assessment (CGA) might provide a less costly alternative to hospitalisation for older people. Objective: to determine the cost-effectiveness of CGA admission avoidance hospital at home (HAH) compared with hospital admission. Design/intervention: a cost-effectiveness study alongside a randomised trial of CGA in an admission avoidance HAH setting, compared with admission to hospital. Participants/setting: older people considered for a hospital admission in nine locations across the UK were randomised using a 2:1 randomisation schedule to admission avoidance HAH with CGA ( N = 700), or admission to hospital with CGA when available ( N = 355). Measurements: quality adjusted life years, resource use and costs at baseline and 6 months; incremental cost-effectiveness ratios were calculated. The main analysis used complete cases. Results: adjusting for baseline covariates, HAH was less costly than admission to hospital from a health and social care perspective (mean −£2, 265, 95% CI: −4, 279 to −252), and remained less costly with the addition of informal care costs (mean difference −£2, 840, 95% CI: −5, 495 to −185). There was no difference in quality adjusted survival. Using multiple imputation for missing data, the mean difference in health and social care costs widened to −£2, 458 (95% CI: −4, 977 to 61) and societal costs remained significantly lower (−£3, 083, 95% CI: −5, 880 to −287). There was little change to quality adjusted survival. Conclusions: CGA HAH is a cost-effective alternative to admission to hospital for selected older people.